GROSS, HISTOPATHOLOGICAL, HISTOENZYMATIC AND HISTOCHEMICAL STUDIES ON INFECTIOUS BURSAL DISEASE IN BROILER CHICKENS - B. M. Wani; M. M. Darzi; S. A. Kamil; S. Shah; S. Adil; T. Ayaşan3 (Journal of Animal and Plant Sciences, 2020)
Immunosuppressive diseases like Infectious Bursal Disease (IBD) required quick and precise diagnosis because of the immense economic losses associated with it. Therefore, a multi-facet diagnostic approach was used to investigate the broiler chicken affected with IBD in Kashmir, India. The full history in terms of chicken population, their age group, symptoms, morbidity, mortality and vaccination schedules were collected. The post-mortem examination of dead birds was done and pathological study was conducted on samples collected. As suggestive of the disease, bursa of Fabricius was mostly affected. Histopathologically, the lymphoid depletion, follicular necrosis, cellular infiltration, congestion and epithelial desquamation were observed in bursal follicles. Histoenzymatic examination revealed scant enzymatic activity in bursa, caeca and in alveolar epithelium of Harderian gland. Histochemically, only glandular epithelial cells and the epithelial areas with inflammatory cell infiltrations were positive for acid mucopolysaccharides. The glandular epithelium of caecum and plical epithelium of bursa were found positive for acid mucopolysaccharides among the lymphoid organs. In conclusion, the bursa of Fabricius was pathologically most affected in IBD diseased broiler chicken. The bursa was enlarged in all the groups, but however, if we compare among different groups, it was haemorrhagic with dark red discolouration in severely affected birds (probably infected with highly virulent strain) and in some group’s bursa was found to be enlarged, filled with catarrhal exudate but not haemorrhagic. No bursal atrophy was found in the present study thus indicating that the disease had started recently because bursal atrophy is detected in advanced cases of IBD. Further, histoenzymatic and histochemical methods were seen to be useful in diagnosis of the IBD in broiler chicken.
Keywords: Broiler; immunosuppression; lymphoid organs; histopathology; histochemistry; histoenzymatic analysis